Why I stand - Isaac, Jonathan, 1997-; Gregory, A. J., 1976- (DW Books, 2022)
On July 31, 2020, the Orlando Magic starting forward Jonathan Isaac was the lone NBA player not to kneel for the national anthem amid a league-wide demonstration in support of Black Lives Matter. In Why I Stand, he shares the journey of how-through a series of divine connections and a willingness to follow Christ-his fear and insecurity-driven life was transformed into one of confidence and purpose.